Partial Anomalous Pulmonary Venous Connection: A Great Imitator? - Rajeev Virender Seecheran MBBS; Taarik Dookie MBBS; Valmiki Krishna Seecheran MBBS; Sangeeta Anjali Persad MBBS; Bryan-Lee Marsang MBBS; Fidel Rampersad MBBS; Paramanand Maharaj MBBS; Naveen Anand Seecheran MBBS, MD, MSc, FACP, FACC, FESC, FSCAI (SAGE Publishing, 2020)
In isolated partial anomalous pulmonary venous connections (PAPVCs), an abnormal vein connects venous blood from the pulmonary circulation to the systemic circulation, resulting in an extracardiac shunt. A single aberrant pulmonary vein (PV) is usually hemodynamically insignificant, and affected patients are generally asymptomatic. We describe a young Caribbean-Black woman with an isolated, singular PAPVC from the left inferior PV to the left innominate (brachiocephalic) vein that was hemodynamically significant, obfuscated by recurrent pleural effusions from catamenial pleural endometriosis.